Reversal Reaction in Leprosy Patients: Study on Prevalence, Sociodemographic Characteristics, and Precipitating Factors at a Tertiary Referral Hospital in West Java, Indonesia - Hendra Gunawan; Risa Miliawati; Renasha Firda Hanannisa (Faculty of Medicine Universitas Padjadjaran, 2022)
Background: Heretofore, leprosy remains one of the most stigmatizing diseases with serious social consequences. Patients with leprosy might develop inflammatory reactions that interrupt with stable and chronic disease which are called leprosy reactions. Type 1 leprosy reactions, also known as reversal reactions (RR), are caused by immune responses that initially decreases, then “reverses” to become more intense, leading to considerable disability. The aim of this study was to identify the prevalence, sociodemographic characteristics, and precipitating factors of reversal reaction in leprosy patients.Methods: This was a retrospective study with a cross-sectional design, with an approach to collecting data from the medical records of the Leprosy Clinic, Department of Dermatology and Venereology Dr. Hasan Sadikin General Hospital Bandung West Java, during January 2015–December 2019.Results: The results showed that 53 patients (24.7%) of the total 214 leprosy patients experienced a reversal reaction. The most frequent type of leprosy with reversal reaction was borderline lepromatous (BL) (56.5%). Most of the patients were male (68%), aged between 25–44 years (47.2%), unemployed patients (35.8%), and the last education was senior high school (71.7%). Physical stress was suspected as the most precipitating factor in reversal reaction patients (50.9%).Conclusions: The prevalence of leprosy patients with reversal reaction in a Tertiary Referral Hospital West Java, Indonesia is 24.7%, with various characteristics based on sociodemographic. Physical stress is suspected as the most precipitating factor of RR in leprosy patients. Early diagnosis of reversal reaction is important to prevent nerve damage and disability.